Efektifitas Kelompok Psikoterapi Positif Untuk Meningkatkan Kesejahteraan Psikologis Pada Narapidana - UTAMI, NINDYA, Dr. Nisa Rachmah N. A, M.Si, Psikolog, Dr. Eny Purwandari, M.Si (2016)
This research aims to know the effectiveness of Group Positive Psychotherapy granting to increasing psychological well-being on inmates. Experimental research using quasi-experimental design models that pretest - posttest control group design with Group Positive Psychotherapy. The subject of this research totaled 12 people inmates are divided into two groups, 5 people as the experimental group and 7 people as control groups. Data analysis using non parametric test Friedman and Mann Whitney U tests. Test result discrepancies pretest and posttest, follow-up score Friedman suggests that intervention Group Positive Psychotherapy showed no significant differences in experimental group before intervention by having given the intervention. Test result is the difference between group experiments with the control group test Mann Whitney U-Test posttest, shows that there was no difference in psychological well-being significant increase between the experimental and the control group. It was concluded that a Group Positive Psychotherapy interventions lacking contribution significantly in providing psychological well-being changes on inmates. Nevertheless, from the sixth dimensions of psychological well-being, there are two aspects that are experiencing increased significantly in dimensions/aspects of independence and self-acceptance.